2021
DOI: 10.1016/j.invent.2021.100453
|View full text |Cite
|
Sign up to set email alerts
|

Individually tailored Internet-delivered cognitive-behavioral therapy for survivors of intimate partner violence: A randomized controlled pilot trial

Abstract: Intimate partner violence (IPV) is a serious public health concern worldwide and defined as behavior performed by spouses or other intimate partners that causes physical, sexual, or psychological harm. Internet-delivered cognitive-behavioral therapy (ICBT) may be particularly useful for survivors of IPV for several reasons, including barriers pertaining to limited community recourses and treatment availability, safety concerns, and issues of stigma, guilt and shame, which may prevent members of this population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…A systematic review was conducted in which eight articles were selected to assess the current empirical evidence of CBT for the treatment of psychological harm in domestically abused women. To begin with, based on the articles selected according to the inclusion and exclusion criteria, the majority of publications have been conducted at the international level (87.5%) (Andersson et al, 2021;Graham-Bermann et al, 2019;Greene et al, 2019;Johnson et al, 2020;Latif et al, 2021;Orang et al, 2018;Osma et al, 2022), compared to the regional (12.5%) (Habigzang et al, 2018); however, at the national level, no studies addressing the proposed topic were found in the databases consulted up to the date of review. Possibly the absence of research in Ecuador on CBT in DV may be attributable to multiple factors such as the lack of funding (governmental or private) for intervention projects, the inexistence of a governing body that regulates the practice of psychotherapists (Guano & Costales, 2021) complete, or pay for a treatment, which will make it difficult to establish processes for research purposes.…”
Section: Resultados Y Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A systematic review was conducted in which eight articles were selected to assess the current empirical evidence of CBT for the treatment of psychological harm in domestically abused women. To begin with, based on the articles selected according to the inclusion and exclusion criteria, the majority of publications have been conducted at the international level (87.5%) (Andersson et al, 2021;Graham-Bermann et al, 2019;Greene et al, 2019;Johnson et al, 2020;Latif et al, 2021;Orang et al, 2018;Osma et al, 2022), compared to the regional (12.5%) (Habigzang et al, 2018); however, at the national level, no studies addressing the proposed topic were found in the databases consulted up to the date of review. Possibly the absence of research in Ecuador on CBT in DV may be attributable to multiple factors such as the lack of funding (governmental or private) for intervention projects, the inexistence of a governing body that regulates the practice of psychotherapists (Guano & Costales, 2021) complete, or pay for a treatment, which will make it difficult to establish processes for research purposes.…”
Section: Resultados Y Discussionmentioning
confidence: 99%
“…Regarding psychotherapy, the selected research is based on CBT; in addition, each one presents particularities that differentiate them from each other. For example, the work conducted by Orang et al (2018) relies on narrative therapy and previous traumatic memories Indeed, all studies (Andersson et al, 2021;Graham-Bermann et al, 2019;Greene et al, 2019;Habigzang et al, 2018;Johnson et al, 2020;Latif et al, 2021;Orang et al, 2018), have focused on addressing PTSD, anxiety, or depression. This finding is similar with a recent systematic review in which all eleven selected studies identified and treated the mentioned pathologies using CBT (Petersen et al, 2019).…”
Section: Resultados Y Discussionmentioning
confidence: 99%
See 3 more Smart Citations